Prevalence of hepatitis D virus infection in Central Italy has remained stable across the last 2 decades with dominance of subgenotypes 1 and characterized by elevated viral replication - Romina Salpini; Lorenzo Piermatteo; Giulia Torre; Stefano D'Anna; Sohaib Khan; Leonardo Duca; Ada Bertoli; Simone La Frazia; Vincenzo Malagnino; Elisabetta Teti; Marco Iannetta; Pierpaolo Paba; et al. (International Journal of Infectious Diseases, 2024)
Objectives: Here we investigate Hepatitis D virus (HDV)-prevalence in Italy and its fluctuations over time and we provide an extensive characterization of HDV-infected patients. Methods: The rate of HDV seroprevalence and HDV chronicity was assessed in 1579 hepatitis B surface antigen (HBsAg)+ patients collected from 2005 to 2022 in Central Italy. Results: In total, 45.3% of HBsAg+ patients received HDV screening with an increasing temporal trend: 15.6% (2005-2010), 45.0% (2011-2014), 49.4% (2015-2018), 71.8% (2019-2022). By multivariable model, factors correlated with the lack of HDV screening were alanine-aminotransferase (ALT) less than two times of upper limit of normality (<2ULN) and previous time windows (P <0.002). Furthermore, 13.4% of HDV-screened patients resulted anti-HDV+ with a stable temporal trend. Among them, 80.8% had detectable HDV-ribonucleic acid (RNA) (median [IQR]:4.6 [3.6-5.6] log copies/ml) with altered ALT in 89.3% (median [IQR]:92 [62-177] U/L).Anti-HDV+ patients from Eastern/South-eastern Europe were younger than Italians (44 [37-54] vs 53 [47-62] years, P <0.0001), less frequently nucleos(t)ide analogs (NUC)-treated (58.5% vs 80%, P = 0.026) with higher HDV-RNA (4.8 [3.6-5.8] vs 3.9 [1.4-4.9] log copies/ml, P = 0.016) and HBsAg (9461 [4159-24,532] vs 4447 [737-13,336] IU/ml, P = 0.032). Phylogenetic analysis revealed the circulation of HDV subgenotype 1e (47.4%) and -1c (52.6%). Notably, subgenotype 1e correlated with higher ALT than 1c (168 [89-190] vs 58 [54-88] U/l, P = 0.015) despite comparable HDV-RNA. Conclusions: HDV-screening awareness is increasing over time even if some gaps persist to achieve HDV screening in all HBsAg+ patients. HDV prevalence in tertiary care centers tend to scarcely decline in native/non-native patients. Detection of subgenotypes, triggering variable inflammatory stimuli, supports the need to expand HDV molecular characterization.